Indoor exposure levels and risk assessment of volatile organic compounds in residences, schools, and offices in China from 2000 to 2021: A systematic review. (18th September 2022) - Liu, Ningrui; Bu, Zhongming; Liu, Wei; Kan, Haidong; Zhao, Zhuohui; Deng, Furong; Huang, Chen; Zhao, Bin; Zeng, Xiangang; Sun, Yuexia; Qian, Hua; Mo, Jinhan; et al.
Abstract: The last two decades have witnessed rapid urbanization and economic growth accompanied by severe indoor air pollution of volatile organic compounds (VOCs) in China. However, indoor VOC pollution across China has not been well characterized and documented. This study is a systematic review of field measurements of eight target VOCs (benzene, toluene, xylenes, acetaldehyde, p ‐dichlorobenzene, butadiene, trichloroethylene, and tetrachloroethylene) in residences, offices, and schools in China from 2000 to 2021. The results show that indoor pollution of benzene, toluene, and xylenes has been more serious in China than in other countries. Spatiotemporal distribution shows lower indoor VOC levels in east and south‐east regions and a declining trend from 2000 to 2021. Moving into a dwelling more than 1 year after decoration and improving ventilation could significantly reduce exposure to indoor VOCs. Reducing benzene exposure is urgently needed because it is associated with greater health risks (4.5 × 10 −4 for lifetime cancer risk and 8.3 for hazard quotient) than any other VOCs. The present study enriches the database of indoor VOC levels and provides scientific evidence for improving national indoor air quality standards as well as estimating the attributable disease burden caused by VOCs in China.